Dva bohemistické časopisy - Čechová, Marie (My University, 2016)
Study briefly introduces and compares two Czech journals: „Bohemistyka“, published in Poland and „Český jazyk a literatura”, published in Czech Republic. Then focuses on the articles of journal „Český jazyk a literatura”, which may attract foreign Bohemists and Czech language lecturers abroad and analyzes texts about Czech for foreigners. Afterwards author discusses linguistically-oriented themes as they are reflected in the development of the journal since 1950’s.
Keywords: Bohemistyka; Český jazyk a literatura; bohemistické časopisy; vzdělávání učitelů češtiny; tematické okruhy; vývoj časopisu